2016
DOI: 10.18203/2320-1770.ijrcog20162675
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study to evaluate risk factors for ectopic pregnancy

Abstract: INTRODUCTIONEctopic pregnancy (EP) is the leading cause of maternal death during the first trimester of pregnancy, accounting for approximately 10% of all pregnancy-related deaths. 1 It still remains a serious health problem for women of childbearing age.2 A ruptured ectopic pregnancy is a true medical emergency. Morbidity due to ectopic pregnancy is in the form of infertility and ectopic recurrence. Although the total number of intrauterine pregnancies has declined over the past three decades, there has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The incidence of previous abortion among the patients wasn't found to be a significant risk factor for ectopic pregnancy in the current study. Most studies show an increased incidence of ectopic among women with a previous history of abortions 6,10,11 , however, the results differ in terms of significance of such relation.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The incidence of previous abortion among the patients wasn't found to be a significant risk factor for ectopic pregnancy in the current study. Most studies show an increased incidence of ectopic among women with a previous history of abortions 6,10,11 , however, the results differ in terms of significance of such relation.…”
Section: Discussionmentioning
confidence: 91%
“…6 Tubal ligation, while proving to be highly effective in preventing intrauterine pregnancies, was found to increase the risk of ectopic in accidental pregnancies in many studies. 6,8,10,14 The overall incidence of ectopic, though reduced among users of oral contraceptive pills, DMPA and emergency contraceptives as revealed by most studies, the failure of such methods was found to be associated with increased incidence of ectopics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies believed that induced abortion did not increase the risk of EP. [13,15] But other studies showed that there was a positive correlation between the number of abortion and EP. [16,17] On the one hand, some researchers believed that induced abortion may lead to some complications such as endometrial lesion and intrauterine adhesion, which may affect the implantation of fertilized egg in the uterus and reduce the pregnancy rate finally.…”
Section: Discussionmentioning
confidence: 99%